Influence of Chemical Structure on the Refractive Index of Imide‐Type Polymers. Issue 21 (5th August 2013) - Butnaru, Irina; Bruma, Maria; Kopnick, Thomas; Stumpe, Joachim
<x xml:space="preserve">Abstract</x> The influence of different substituents on the optical properties of poly(amide imide)s and polyimides is systematically investigated. All of the polymers exhibit good solubility and film‐forming ability, high thermal stability, and glass transition temperatures of 162–209 °C for poly(amide imide)s and of 209–274 °C for polyimides. The optical transmittance of the films at 450 nm is above 80% for all the studied polyimides and poly(amide imide)s containing benzonitrile units linked in the 2, 6‐position. The values of refractive index for poly(amide imide)s are in the range of 1.623–1.748 and for polyimides in the domain of 1.672–1.768. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>